Inside Cover: Persistent Organic High‐Spin Trinitrenes (Angew. Chem. Int. Ed. 37/2019). Issue 37 (30th July 2019) - Mendez‐Vega, Enrique; Mieres‐Perez, Joel; Chapyshev, Sergei V.; Sander, Wolfram
Abstract : Surprisingly stable organic trinitrenes were synthesized in almost quantitative yields from their triazide precursors. In their Communication on page 12994 ff. W. Sander et al. show that the trinitrenes with six unpaired electrons and septet electronic ground states can be synthesized in inert matrices and in amorphous water at cryogenic temperatures. Under these conditions they are stable towards oxygen, hydrogen, and water, which makes these molecules promising building blocks for the design of organic magnetic materials.